Plastic Surgery In Kangra (A leaf from the history of Plastic Surgery in India) - S. C. Almast (Indian Journal of Plastic Surgery, 1969)
Plastic surgical operations for cut and deformed noses and torn ears had been practised at Kangra for over 500 years by a family of nose-surgeons locally called Kanghairas. Hakim Dina Nath is the last surviving descendant of the faimily who himself performed these operations till 1937. This paper is a report of the “on the spot” inquiry conducted by the author to verify the facts for himself.